The Effect of Gestational Weight Gain on Low Birth Weight, Case-Control Study in Northeast Amhara Regional State, Ethiopia, 2019 - Mezen, Muluemebet Kassa; Lemlem, Getasew Assefa; Biru, Yemisrach Belete (International Journal of Child Health and Nutrition, 2022)
Background: Intrauterine growth and development are one of the most vulnerable periods in the human life cycle that contribute to appropriate fetal development. Therefore, this study aimed to assess the effect of gestational weight on low birth weight (LBW). Methods: A case-control study was conducted from June 30, 2018, to January 1, 2019, in seven governmental hospitals in the northeast Amhara region on 451 participants(150 cases and 301 controls). Results: Inadequate gestational weight gain increases the risk of LBW by four times (AOR: 4.2, 95% CI: 2.4, 6.4). Anemic mothers were 3 times (AOR: 3.2, 95%CI: 2.5, 5.1) more likely to give birth to LBW newborns than non-anemic women. Mothers with a height of less than 150 cm were 2 times more likely to deliver low birth weight babies than their counterparts (AOR:2.1, 95% CI: 1.5,4.4). The odds of LBW delivery were 3.5 times (AOR: 3.5, 95% CI: 2.3, 5.3) higher for mothers with poor dietary diversity than for mothers with good dietary diversity. Conclusion: Inadequate gestational weight gain during pregnancy was found to be a risk factor for LBW. Additionally, anemia, short stature, and poor dietary diversity were also risk factors for LBW. Therefore, selectively targeted interventions such as improving maternal nutrition, anemia prevention, and proper maternal weight monitoring during pregnancy are needed.